2017
DOI: 10.3177/jnsv.63.1
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Vitamin D Deficiency Is Associated with the Immune Response in Children with Community-Acquired Pneumonia

Abstract: SummaryTo investigate vitamin D status in children with community-acquired pneumonia (CAP) and explore the association between vitamin D deficiency and the immune response in CAP children, 77 children with CAP were retrospectively analyzed. The baseline characteristics of patients were obtained from medical records. Based on the blood samples collected during diagnosis of CAP, the routine blood examination results and proportions of lymphocyte subsets were assessed. There were 71.4% (55/77) of patients with vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…In addition, our results showed that the neutrophil‐to‐lymphocyte ratio was also not significant correlated with vitamin D in stroke patients, while a recent investigation conducted in adolescent girls has observed a significant reduction in neutrophil‐to‐lymphocyte ratio after high‐dose vitamin D supplementation (Tabatabaeizadeh et al., ). Another observational study conducted in children with community‐acquired pneumonia (CAP) has found that vitamin D deficiency had a significantly higher neutrophil‐to‐lymphocyte ratio distribution (Huang, Fu, & Yang, ). The relationship between neutrophil‐to‐lymphocyte ratio and vitamin D has not been discussed in stroke patients before the study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results showed that the neutrophil‐to‐lymphocyte ratio was also not significant correlated with vitamin D in stroke patients, while a recent investigation conducted in adolescent girls has observed a significant reduction in neutrophil‐to‐lymphocyte ratio after high‐dose vitamin D supplementation (Tabatabaeizadeh et al., ). Another observational study conducted in children with community‐acquired pneumonia (CAP) has found that vitamin D deficiency had a significantly higher neutrophil‐to‐lymphocyte ratio distribution (Huang, Fu, & Yang, ). The relationship between neutrophil‐to‐lymphocyte ratio and vitamin D has not been discussed in stroke patients before the study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were observed even in children with CAP. These patients with vitamin D deficiency had a significantly higher neutrophil percentage, but significantly lower lymphocyte percentage and hence vitamin D deficiency could affect the immune response in children with CAP . We did not find differences in the other biochemical determinations when the groups were stratified according to 25OHD levels.…”
Section: Discussionmentioning
confidence: 55%
“…In patients with recurrent miscarriage, the percentage of CD19 + B cells was significantly higher in the vitamin D 3 insufficiency group than in the vitamin D 3 normal group [30]. In children with community-acquired pneumonia, the positive CD19 + cells in patients with vitamin D deficiency were significantly less than that in patients without vitamin D 3 deficiency [31]. We first reported the evidence linking vitamin D level and CD19 in CHB patients.…”
Section: Discussionmentioning
confidence: 98%